expantion of log(1-x)
Answers
Answered by
0
TMC !!!!!!!!!!!!!!!!!!!!
Answered by
0
hey mate this is your answer-
Of course you can. But using that method you only obtain the Taylor series of f(x)=log(1+x)f(x)=log(1+x), that is ∑n=1∞(−1)n−1xnn∑n=1∞(−1)n−1xnn. To prove that log(1+x)=∑n=1∞(−1)n−1xnnlog(1+x)=∑n=1∞(−1)n−1xnn in (−1,1)(−1,1)(also in x=1x=1) you need to verify that the remainder of the Taylor series converges to 0
Of course you can. But using that method you only obtain the Taylor series of f(x)=log(1+x)f(x)=log(1+x), that is ∑n=1∞(−1)n−1xnn∑n=1∞(−1)n−1xnn. To prove that log(1+x)=∑n=1∞(−1)n−1xnnlog(1+x)=∑n=1∞(−1)n−1xnn in (−1,1)(−1,1)(also in x=1x=1) you need to verify that the remainder of the Taylor series converges to 0
Similar questions
Math,
7 months ago
Music,
7 months ago
Computer Science,
7 months ago
English,
1 year ago
Biology,
1 year ago